Kuliner Halal dan Higenis Menurut Islam - Husnul Amin; Ahmad Arifai (SALIHA: Jurnal Pendidikan & Agama Islam, 2020)
Al-Qur'an is a revelation of God revealed to the Prophet, In the Koran itself, certainly not a few verses of the Koran that talk about various things, including about food. To be able to understand the meaning of the concept of food in the Koran and Hadith is to collect all texts and analyze them. The attention of the Koran and the traditions of hygiene and cleanliness is not only with ablution and bathing alone. However, both are very concerned about other hygiene needed by humans. Food, clean water are important things that support human health. Most people are attacked by diseases due to consuming unhygienic snacks due to the mixing of food with street dust so as to grow bacteria.